DIFFERENCES IN CONSUMPTION OF JANTUNG PISANG (MUSA PARADISIACA) AND DAUN KELOR (MORINGA OLEIFERA) TOWARDS BREAST MILK PRODUCTION IN BREASTFEEDING MOTHERS IN THE WORK AREA OF PUSKESMAS NORTH BENGKULU - Rolita Efriani; Desi Widiyanti; Eliana Eliana; Diah Eka Nugraheni; Sella Oktarika (Poltekkes Kemenkes Bengkulu, 2022)
The number of exclusive breastfeeding in the world is only 44 percent. Exclusive breastfeeding coverage in Indonesia is 65.16 percent. This coverage is still far from the target in Indonesia of 95 percent. The coverage of exclusive breastfeeding in Bengkulu Province in 2020 is 73 percent, and the coverage of breastfeeding in North Bengkulu Regency is 73.81 percent. This study aims to determine the difference between consumption of musa paradisiaca and moringa oleifera on breast milk production in breastfeeding mothers in the Work Area of the North Bengkulu Regency Health Center. The study used experimental research methods. The population is postpartum mothers on the 5th day in December 2021 - January 2022 in the working area of the North Bengkulu Regency Health Center with a total of 57 people. The sample amounted to 46 respondents, 23 for the musa paradisiaca consumption group and 23 for the moringa oleifera consumption group. Respondents were taken by accidental sampling technique. Data were analyzed by bivariate analysis using independent T-test. Results: Most of the intervention group had parity multipara and grandemultipara (78.3%), almost half of them had secondary education (47.8%), and most of the families supported breastfeeding (60.9%), while in the comparison group, most of with parity multipara/grandemultipara (69.6%), more than half of them have basic education (52.1%), and most families support breastfeeding (69.6%); The average milk production in the musa paradisiaca group was 454.36 meanwhile, the moringa oleifera group was 358; There was a difference in consumption of jantung pisang (musa paradisiaca) and daun kelor (moringa oleifera) to increase breast milk production (p = 0.001). The results of this are expected to provide input for Puskesmas to increase promotion and motivation of exclusive breastfeeding mothers to improve maternal and child health.